All I want for Christmas - Knox, Maggie (G.P. Putnam's Sons, 2022)
"A pitch-perfect holiday rom com about two oil-and-water reality-star country singers who must fake a relationship in order to win the opportunity of a lifetime, perfect for fans of Sally Thorne's The Hating Game and Christina Lauren's In a Holidaze"--